Australia's Bankrupt Chinese Furniture Manufacturers, 1880–1930. (27th July 2017) - Gibson, Peter
Abstract : The proprietors of almost 100 Chinese furniture factories in Australia went bankrupt during the late nineteenth and early twentieth centuries. With a substantial stake in furniture production for decades following the gold rushes of the 1850s and 1860s, Chinese furniture factory operators were vilified and legislated against in a push for 'White‐Australian' industrial advancement. Historians have consistently concentrated on such campaigns when explaining Chinese‐Australian business failures of this period. Yet informed principally by their bankruptcy court testimony, this paper contends that Chinese furniture manufacturers went bankrupt largely because of economic difficulties and, thus, failures are not sufficiently explained by 'White Australia'.